2018
DOI: 10.1002/cbic.201800280
|View full text |Cite
|
Sign up to set email alerts
|

Azide‐ and Alkyne‐Bearing Metabolic Chemical Reporters of Glycosylation Show Structure‐Dependent Feedback Inhibition of the Hexosamine Biosynthetic Pathway

Abstract: Metabolic chemical reporters (MCRs) of protein glycosylation are analogues of natural monosaccharides that bear reactive groups, like azides and alkynes. When they are added to living cells and organisms, these small molecules are biosynthetically transformed into nucleotide donor sugars and then used by glycosyltransferases to modify proteins. Subsequent installation of tags by bioorthogonal chemistries can then enable the visualization and enrichment of these glycoproteins. Although this two-step procedure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Fourth, previous publications indicated a specific role of the N-acetyl moiety of UDP-GlcNAc in inhibition, which points towards the interdomain linker: Assrir et al 33 reported that UDP and UDP-Glc do not inhibit GFAT-1, but are able to bind with a similar K D as for UDP-GlcNAc. Moreover, Walter et al 46 generated metabolic chemical reporters with large azide-or alkyne- residues at the N-acetyl position, which also failed to inhibit GFAT-1 46 . Together, these publications emphasize the role of the N-acetyl group in inhibition whose only possible interaction partner are residues from the interdomain linker, especially Gln307 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, previous publications indicated a specific role of the N-acetyl moiety of UDP-GlcNAc in inhibition, which points towards the interdomain linker: Assrir et al 33 reported that UDP and UDP-Glc do not inhibit GFAT-1, but are able to bind with a similar K D as for UDP-GlcNAc. Moreover, Walter et al 46 generated metabolic chemical reporters with large azide-or alkyne- residues at the N-acetyl position, which also failed to inhibit GFAT-1 46 . Together, these publications emphasize the role of the N-acetyl group in inhibition whose only possible interaction partner are residues from the interdomain linker, especially Gln307 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any changes to the endogenous production of the natural repertoire pool of donor nucleotide sugars might affect GFAT binding and/or catalytic activity. Very interestingly, unnatural GalNAc analogues (e.g., GalNAz and GalNAlk) that have larger substitutions at the 2- N -acetyl position do not appreciably inhibit GFAT, whereas unnatural GlcNAc analogues (e.g., GlcNAz and GlcNAlk) having an extended size of the N -acetyl position appear to prevent inhibition of GFAT . In contrast, GFAT is inhibited (with varying degree) by the corresponding UDP sugars from either hexosamine analogues with azide/alkyne substitutions at other positions (e.g., 6AzGalNAc) or glucose derivatives (e.g., 2AzGlc and 6AzGlc) .…”
Section: Characterization Of Individual O-glcnac Proteinsmentioning
confidence: 99%
“…They are consistent with our published observation that increased steric bulk at the N-acetyl position of UDP-GlcNAc or UDP-GalNAc, such as an azide, prevented feedback inhibition of GFAT. 23 Finally, we used an MTT assay to show that Ac 3 4FGalNAz was not toxic to cells at 50 μM and displayed a similar toxicity to Ac 4 GalNAz at 200 μM ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 19 22 However, we have shown that azido-substitution of the N-acetyl position of different UDP sugar blocks this feedback mechanism. 23 With these data in mind, we reasoned that Ac 3 4FGalNAz could be converted to UDP-4FGalNAz by endogenous enzymes and be incompatible with epimerization by GALE ( Figure 2 ), preventing the formation of the GlcNAc epimer. Several studies have found that OGT can transfer UDP-GalNAc to peptide substrates but at significantly lower efficiency compared to UDP-GlcNAc.…”
Section: Introductionmentioning
confidence: 99%